THE EFFECTIVENESS OF NON VERBAL COMMUNICATION IN TEACHING AND LEARNING ENGLISH: A SYSTEMATIC REVIEW - Paranduk, Rida; Karisi, Yofri (Journal of English Culture, Language, Literature and Education, 2020)
In the reviewed studies non verbal communication used by teachers in teaching English The purpose of this research is to study the type of Non verbal communication by English teachers in teaching and to finding out how English teachers use non verbal communication in teaching class much further whether to seek out the strength and weaknesses of the non verbal communication and to find out the effective way to use non verbal communication efficiently and effectively This research used a Quantitative approach which the efforts are to collect all of the studies that shared the common field of the study The result of this study showed that the benefits the advantages the disadvantages and its effects Moreover the non verbal communication give some contributions in education which can be applied by teacher today Recommendation and suggestion are offered in the current study Hence non verbal communication is recommended to be used by teacher in this classroom < p>